Cardiovascular inhibitory properties of Lens culinaris - Munasib Khan; Arif-ullah Khan; Najeeb-ur Rehman; Anwarul-Hassan Gilani (Bangladesh Pharmacological Society, 2014)
In present study, we report the blood pressure lowering, vasodilatory and cardio-depressant activities of Lens culinaris. The crude extract of L. culinaris induced dose-dependent (3-30 mg/kg) fall in the arterial pressure of rats under anesthesia. When tested in rat aortic ring preparations, L. culinaris at concentration range of 0.03-5.0 mg/mL relaxed high K+ (80 mM) and phenylephrine (1 ?M)-induced contractions, like that caused by verapamil. In isolated guinea-pig atria, L. culinaris caused inhibition of atrial force and rate of spontaneous contractions, similar to that exhibited by verapamil. These data indicate that L. culinaris exhibits blood pressure lowering potential, mediated possibly through Ca++ channel blockade mechanism.